1983
DOI: 10.1073/pnas.80.22.6977
|View full text |Cite
|
Sign up to set email alerts
|

Arylsulfatase in natural killer cells: its possible role in cytotoxicity.

Abstract: Ultrastructural cytochemistry of natural killer cells enriched by Percoll gradient centrifugation showed them to possess arylsulfatase (aryl-sulfate sulfohydrolase, EC 3.1.6.1). The enzyme was located in vesicles, granules, and the parallel tubular arrays, organelles characteristic for cytotoxic lymphocytes. Biochemically, peak enzyme activity correlated with the Percoll fractions containing cells with cytotoxicity for melanoma target cells. Treatment of natural killer cells with Na2SO4, a competitive inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Previous work had established the subcellular distribution of a number of lysosomal hydrolases in NK cells (12)(13)(14). Although all these enzymes presumably bear phosphomannose, they are present in type II granules and the cortical regions of type I granules, a distribution opposite that of the similarly modified serine proteases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work had established the subcellular distribution of a number of lysosomal hydrolases in NK cells (12)(13)(14). Although all these enzymes presumably bear phosphomannose, they are present in type II granules and the cortical regions of type I granules, a distribution opposite that of the similarly modified serine proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Like lysosomes, the granules are acidic (9), although this is also a property of secretory granules (3). In addition, NK granules contain many "classical" lysosomal hydrolases, including acid phosphatase, f3-glucuronidase, and aryl sulfatase (12)(13)(14). Indeed, histochemical assays of these enzymes are often used to identify large granular lymphocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that AS participates in the cytolytic activity of NK cells towards SRBC [19] and melanoma cells [18]. We studied the cytolytic and bactericidal activities of resting and IL-2-or IL-7-stimulated NK cells against K562, Daudi cells, and E. coli and investigated to what extent AS plays a role in the lytic process of effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several anions are inhibitors of the enzyme, including SO 4 2P , SO 3 2P , and PO 4 3P . The enzyme is known to play a role in granulocytic [17] and NK function [18]. It has been shown that AS is involved in the degradation of cerebroside sulfate esters, likely membrane components of most target cells, and that it participates in the cytolytic activity of NK cells towards melanoma cells [18] and sheep red blood cells (SRBC) [19].…”
Section: Introductionmentioning
confidence: 99%